The Chinese model of modern development - Cao, Tian Yu, 1941- (Routledge studies on the Chinese economy., 2005)
This book examines the Chinese model of modern development, reflecting on the historical experience of China's reform, and highlighting theoretical issues that are crucial for understanding the reform in its historical and global contexts.